Pengenalan Konsep Saham Syariah Dalam Menggerakkan Investasi Syariah Pada SMK Budi Agung Medan - Arafah, Santi (Dinamis: Jurnal Pengabdian Kepada Masyarakat, 2022)
The capital market is used as an effective means of mobilizing public funds to be further channeled into productive activities. Public funds that enter the capital market are long-term funds. And the capital market that develops in a country should be good (healthy). Over time, BAPEPAM-LK (Capital Market Supervisory Agency-Financial Institutions) with the National Sharia Council-Indonesian Ulema Council (DSN-MUI) officially launched the Islamic capital market. Islamic stock is one of the products traded in the Islamic capital market. This Islamic stock emphasizes the prohibition of transactions in which there is speculation and contains gharar or obscurity, namely transactions in which fraud is possible (khida’). The presence of sharia shares aims to increase public participation so as to promote people’s economic efforts, including expanding the network of Islamic financial institutions to remote areas. The purpose of this PKM is to educate and guide people to think economically, behave in business and improve their quality of life, especially for students of SMK Budi Agung Medan.